ABDULLA AVLONI (Conference Zone, 2022)
Abdulla Avloni is a writer, public figure and talented pedagogue who has made a great contribution to the development of art and literature of the Uzbek people, as well as national culture and public education. Abdulla Avloni was one of the first Uzbek intellectuals. In 1913, he organized a theater troupe called Turon to turn the Uzbek People's Theater into a professional theater. However, there were major obstacles for the troupe to become a professional theater. The colonial policy of the tsarist government was against all forms of theater that helped to awaken the social consciousness of the people.